Evaluating the effect of the competition between NbC precipitation and grain size evolution on the hot ductility of Nb containing steels. - Furumai, Kohei; Wang, Xiang; Zurob, Hatem; Phillion, Andre (ISIJ International, 2019)
The hot ductility of steels containing 0-0.06wt.%Nb has been evaluated through γ grain growth experiments and hot stage tensile tests of the α+γ two phase region in order to clarify the roles of NbC precipitation and γ grain size evolution resulting from Nb initiated solute drag on hot ductility in this important material property. The experimental results show that (1) a decrease in γ grain size as a result of Nb-initiated solute drag improves hot ductility, (2) for a given 𝛾 grain size, hot ductility decreases with increasing Nb content because the corresponding increase in NbC precipitation fraction increases strength, and (3) the variation in ductility with Nb content is smaller when the 𝛾 grain size is smaller. These competing effects of γ grain size and NbC precipitation affect the strain incompatibility between the α and γ phases, leading to the onset of surface cracking during continuous casting when the incompatibility is high. The underlying mechanisms controlling ductility in Nb-containing steels are demonstrated using a model that partitions strain between the α and γ phases.
Keywords: Continuous Casting; Nb-containing steel; austenite grain growth; ferrite and austenite phases; precipitation; ductility; crack